2021
DOI: 10.3389/fpubh.2021.782251
|View full text |Cite
|
Sign up to set email alerts
|

To Stay or to Leave? Migrant Workers' Decisions During Urban Village Redevelopment in Hangzhou, China

Abstract: As a vital source of the demographic dividend, migrant workers living in urban villages have positively contributed to urban economic development and the improvement of urbanization. Although urban villages have had a great impact on public health due to the shabby environments and poor public safety, the large-scale demolition of the urban villages, the supply of affordable housing for migrant workers has decreased drastically, which may lead to the outflow of many migrant workers and consequently affects the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…It is also worth noting that migrant workers will inevitably experience a sense of social conflict in the process of urban integration [49,50]. This study finds that the sense of social conflict will regulate the impact of economic public service satisfaction on the sense of social equity but cannot regulate the impact of social public service satisfaction on social equity.…”
Section: Discussionmentioning
confidence: 82%
“…It is also worth noting that migrant workers will inevitably experience a sense of social conflict in the process of urban integration [49,50]. This study finds that the sense of social conflict will regulate the impact of economic public service satisfaction on the sense of social equity but cannot regulate the impact of social public service satisfaction on social equity.…”
Section: Discussionmentioning
confidence: 82%
“…Based on the current results, although the government has made great efforts to promote fuel revolution in the past decades[ 36 ], there is still a neglectable proportion of urban residents who were still using solid fuels in their household life, which did lie a huge burden on health and well-being. It could partly be explained that there are a lot of “urban villages” currently in China, people who live here tend to have a poor environment and public health safety[ 37 ]. Thus, future fuel improvement policies should still pay more attention to people who live in urban areas, especially in urban villages, not only in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…During the interview, construction worker Hong Jian suggested that, like himself, many of his colleagues who also live in Baishizhou have no choice but to leave Shenzhen even before the construction project finishes. The outflow of many migrant workers who work in essential labor-intensive industries threatens the sustainable operation of Shenzhen as it compromises the city's service level and reduces the city's competitiveness [10].…”
Section: Exclusion and Displacementmentioning
confidence: 99%